#TITLE_ALTERNATIVE# - IRFANSYAH (NIM : 23607006); Tim Pembimbing: Dr. Ir. Ichsan Setya Putra Dr. Ir. Tatacipta Dirgant, ADE
Universal Maintenance Center (UMC) or PT. NTP often experiences damage and efficiency degradation of the Rolls-Royce TAY 650-15 turbofanÃ‚Â’s fan blade they had received from their customers. These usually are coating erosions, cracks, and corrosions. According to the guidelines of Structural Repair Manual (SRM), the procedural reparation must be performed for the damaged blade due to erosion and other object impact (notch). The most popular technique to vanish the notch is scallop. This technique grinds the flawed are to smooth down the geometry discontinuity, so the stress concentration could be reduced. If the scallop depth exceeds the SRM restrictions, the structure could be in danger. This thesis will analyze the impact of scalloping technique toward the fatigue life using Finite Element Method. This method models the fan blade into a plate 2D model and a solid 3D model having through crack in thickness direction. The 2D modeling purpose is proofing the truth of geometry factor computation using numerical method. The computed geometry factor is then confronted with handbook reference data with similar geometry. After the 2D model has been proven true, the next step will be the analysis of the through-crack growth of solid 3D model with pure centripetal force. For 8.000 rpm centripetal force, the fatigue life of scalloped-plate 2D model is 17.600 cycle and the scalloped-solid 3D model has 16.300 cycle. The factorystandard fatigue life of non-scalloped fan blade is 20.000 cycle.